Estrategias innovadoras que promueven el desarrollo de la lectura crítica de textos, en estudiantes del nivel primaria en una institución educativa privada de Breña - Rojas Mendoza, Karla Emma (2022)
Looking at the social and political reality that is lived today in our country, it is necessary to form critical citizens capable of questioning and transforming the reality in which they find themselves. One of the means by which the integral formation of the person can be achieved, in addition to the education received at home, is through school education in its different educational levels. Teaching to read comprehensively and critically is an essential aspect of Regular Basic Education, but on many occasions this process is neglected, and the importance of this process is underestimated. For this reason, the present research addresses reading from the sociocultural conception, called critical reading, and its objective is to analyze the innovative strategies that promote its development in primary school students in a private educational institution in Breña. The research is qualitative descriptive. Data were collected through interviews with primary school teachers in order to identify the conception of critical reading that guides their pedagogical work, as well as to identify and describe the strategies they apply in this process.